Composição e diversidade da fauna edáfica sob sistema de sucessão e rotação de culturas associadas ao uso de plantas de cobertura - Tolfo, Erivelto Folhato (2022)
Edaphic fauna is an important component of soil biodiversity and is being altered by agricultural cropping systems. These organisms present great diversity, contributing to important environmental services and to the biological quality of the soil, being used as bioindicators in agroecosystems. Edaphic invertebrates are extremely sensitive to environmental changes, responding quickly to management operations, clearly reflecting how conservationist a practice can be considered. The evaluation of these organisms makes it possible to determine which taxonomic groups are present and which functions they play in different agroecosystems. In this sense, this work aims to evaluate the abundance and diversity of edaphic fauna in crop rotation and succession systems associated with the use of cover crops. The study was carried out at the experimental farm of the Federal University of Technology - Paraná at the Dois Vizinhos, in three different periods in an area of 3 hectares with four production systems distributed in 12 plots, with subplots of different crop species at certain times of the year. . For the determination of chemical and physical soil taxes, soil samples were obtained at a depth of 0-10 cm. The edaphic fauna was sampled with 72 pitfalltraps. The classification of organisms was carried out at the level of large taxonomic groups (Order or Family). The collections took place in August and December 2020 and in April 2021. The data obtained were subjected to Permutational Multivariate Analysis of Variance (PERMANOVA) to test the differences in the composition of the functional groups of the edaphic fauna, considering the effect of subplots, systems and sample periods. Richness and abundance values were used to determine the ecological indices, which were submitted to the Shapiro-Wilk normality test and to the analysis of variance, and compared by the Tukey test at 5% probability. Seeking to understand the relationship between edaphic organisms and chemical attributes, a Canonical Correlation Analysis was performed. A total of 100,719 individuals were identified, distributed in 19 taxonomic groups. The Order Coleoptera presented 1,142 individuals, distributed in 12 families. Regarding the composition of the edaphic fauna, the PERMANOVA multivariate analysis showed that there was no statistically significant difference between the subplots on the composition of the edaphic fauna and for families of the order Coleoptera. However, in relation to the systems, there was a statistically significant difference in all collections. Still regarding the composition of the edaphic fauna, PERMANOVA indicated significance for the seasonality factor. Crop rotation and succession systems associated with the use of cover crops similarly influence the diversity and abundance of edaphic fauna. The different collection times influence the edaphic fauna, mainly due to the food supply at each sampling time. Soil chemical attributes are correlated with the distribution of edaphic fauna.